280 PERCEIVED NEED FOR A CLINICAL ETHICS SUPPORT SERVICE AT AN IRISH UNIVERSITY HOSPITAL. (25th October 2022) - O'Donovan, M; Crowley, P; Flanagan, E; McManus, C; Moloney, E; Favier, C; McKiernan, M; Cornally, N; Campbell, L; O'Connor, K; O'Caoimh, R
Abstract: Background: Ethics are the set of moral principles that guide a person's behaviour. Ethical issues are a key component of healthcare and frequently arise in the management of hospitalized older patients. To improve decision-making and reduce burden on individual hospital staff, Clinical Ethics Support Services (CESS) have been widely-integrated into care pathways internationally. However, the need for CESS has received little attention in Irish hospitals. Methods: A cross-sectional analysis of the ethical situation and CESS readiness at a tertiary hospital in Ireland was collected from July-October 2021 and in February 2022 via hard copies and online collection (SurveyMonkey). Both clinical (medicine, nursing other patient care role) and non-clinical (administrative, clerical, ICT, HR, general support staff and management) staff participated. Descriptive statistics were assessed taking the valid percentages, mean 5-item Likert scores and Friedman Test mean rank for ten ranked statements. Results: In total, 199 people (13% response rate) completed the survey. Staff were largely (76%) clinical and the majority were qualified >10 years (57%). In all, 78% reported that ethical issues arise in the role (83% clinical staff, 59% non-clinical staff). Most (63%) were unsure who to contact about ethical concerns, instead seeking informal advice from colleagues (>90%). The majority of participants were interested in additional ethical training, especially on decision-making capacity (mean interest 4.18 out of 5), strategies for working with challenging patient/family situations (4.07 out of 5) and end-of-life care (4.06 out of 5). Out of ten options assessed, participants preferenced the development of a formal clinical ethics committee over education and training or the provision of educational materials. Conclusion: Ethical issues commonly arise when caring for older hospitalized patients. This study found a perceived need and widespread interest in additional education as well as formal approaches to develop a hospital-based CESS, centred around a formal committee structure.